THE UNSPOKEN VOICE: THE EXPERIENCE OF EMOTIONAL EXPRESSION THROUGH JOURNALING AMONG MALE COLLEGE STUDENTS - Wardah Hafizhah; Yasintha Sari Pratiwi; Iin Andini Ismail; Rizky Amayana Saputri (Jurnal Konseling Pendidikan Islam, 2026)
This study aims to understand the subjective experience of male students in using journaling as a means of expressing emotions. Previous research has focused more on journaling as an intervention, while individual experiences in undergoing the process, particularly in male students, are still limited to study. This study uses a qualitative approach with Interpretative Phenomenological Analysis (IPA) analysis. Three male students who had been journaling regularly for at least three years were selected through purposive sampling. Data were collected through semi-structured in-depth interviews and analyzed following the stages of science. The results show that journaling functions as a private, safe, and reflective space that allows for the expression of emotions without social judgment. This practice facilitates the release of emotions, supports self-reflection, and allows for the negotiation of internalized masculinity norms in a non-confrontational manner. These findings confirm the relevance of journaling in the context of guidance and counseling and expand the study of masculinity by showing that the expression of emotions can take place through internal processes.